Viral‐specific cytotoxic T‐cell responses in HLA‐sensitized kidney transplant patients maintained on everolimus and low‐dose tacrolimus. Issue 2 (3rd March 2022) - Ge, Shili; Chu, Maggie; Tang, Jacqueline; Kahwaji, Joseph; Karasyov, Artur; Lovato, Darly; Vo, Ashley; Choi, Jua; Jordan, Stanley C.; Zhang, Ruan; Toyoda, Mieko
Abstract: Background: Maintenance with "everolimus + reduced dose tacrolimus" (Ev + Taclow ) was reported to reduce the risk of viral infections compared to "tacrolimus + mycophenolate mofetil" (Tac + MMF). Here we examined viremia and viral‐specific T‐cell (viral‐Tc) responses in patients treated with Ev + Taclow versus Tac + MMF in highly‐human leukocyte antigen (HLA)‐sensitized patients. Methods: HLA‐sensitized (HS) kidney transplant patients were monitored pre‐ and post‐transplant for viremia (cytomegalovirus (CMV), BK, and Epstein–Barr virus (EBV)) by polymerase chain reaction (PCR) in 19 Ev + Taclow and 48 Tac + MMF patients. For CMV PCR analysis, we compared infection rates in 19 Ev + Taclow patients to 48 CMV D+/R‐ (#28) or CMV D‐/R‐ (#20) Tac + MMF patients. CMV‐specific cytotoxic T cell (CMV‐Tc) and EBV‐specific cytotoxic T cell (EBV‐Tc) were evaluated by cytokine flow cytometry, and donor‐specific antibody (DSA) levels by Luminex for selected patients in both groups. Results: CMV and EBV viremia rates were similar in Ev + Taclow versus Tac + MMF patients, but BK virus (BKV) rates were significantly higher in Ev + Taclow patients. No patient in either group developed BK virus‐associated allograft nephropathy (BKAN) or post‐transplant lymphoproliferative disorders (PTLD). CMV‐Tc and EBV‐Tc decreased significantly after alemtuzumab induction but returned to pre‐treatment levels 1–2 months post‐transplant in most patients. de novo DSA was similar in both groups as were patient and graft survival and graft rejection. Conclusions: CMV‐Tc and EBV‐Tc were similar in Ev + Taclow and Tac + MMF patients. EBV and CMV viremia rates were similar over 1 year. BKV rates were significantly higher in Ev + Taclow patients suggesting no benefit for Ev + Taclow in enhancing viral‐Tc effector functions or limiting viral infections.